2010
DOI: 10.1111/j.1447-0756.2009.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of therapeutic intervention to prevent mother to child transmission of HIV in a teaching hospital in Kolkata, India

Abstract: As uptake of testing is high and detection of HIV-infected women in pregnancy remains very low, a radical rethinking of policies on therapeutic intervention and their implementation now needs to be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…In this present study, the overall acceptance of HIV testing after counseling with 'opt-out' approach was 98.97% (11,390/11,508). Similar acceptance rate of 100% and 96% was reported by Parameswari et al and Chaudhari et al in India respectively 8,9 . Study conducted by Joshi et.al.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this present study, the overall acceptance of HIV testing after counseling with 'opt-out' approach was 98.97% (11,390/11,508). Similar acceptance rate of 100% and 96% was reported by Parameswari et al and Chaudhari et al in India respectively 8,9 . Study conducted by Joshi et.al.…”
Section: Discussionsupporting
confidence: 74%
“…Similar seroprevalence of 0.56%, 0.41%, and 0.40% was reported by Mandal et al, Giri et 8,15 . Also the lower prevalence of 0.17% was reported by Chaudhari et al 9 . This wide variability in HIV seroprevalence among antenatal women may be attributed to the difference in health seeking and risk behaviors in different parts within and outside India which mostly depends on socio cultural milieu of the community.…”
Section: Sd-standard Deviation Ci-confidence Intervalsmentioning
confidence: 73%
“…10 The WHO and UNAID introduced a routine opt-out approach in countries with high prevalence. 11 In the present study, the overall acceptance of the HIV testing with opt-out approach was 83.85% (15, 14,15 This emphasizes there is need for good counseling skills by the counselor to achieve both counselling and HIV testing close to 100%. We observed that, majority of seropositive pregnant women were married, primigravidae, residence of rural areas with low socioeconomic status, were either illiterate or studied up to primary level and not used any contraceptives.…”
Section: Discussionmentioning
confidence: 93%
“…As on 31 st August 2016 in India there are 20,756 Integrated Counselling and Testing Centres (ICTC), most of these in government hospitals, which offer PPTCT services to pregnant women. 9 Globally over the past few years the PPTCT interventions have transitioned from the use of single dose Nevirapine to the use of multidrug antiretroviral therapy, to efficiently bring down the rate of transmission of HIV from mother-to-child to the level of less than 5%.7 Screening of HIV in pregnant women plays the most important role in reducing mother to child 15,16 To achieve high rates of counselling and testing, good counselling skills and experience of the counsellor is fundamental.…”
Section: Discussionmentioning
confidence: 99%